1988
DOI: 10.1007/bf00914174
|View full text |Cite
|
Sign up to set email alerts
|

The Hopelessness Scale for Children: Psychometric properties with normal and emotionally disturbed adolescents

Abstract: The psychometric properties of the Hopelessness Scale for Children (HSC) were evaluated with a sample of 834 normal adolescents and 93 adolescent suicide attempters. Factor analyses studies revealed two factors with both groups. Internal consistency with item-total score correlations were acceptable, while moderate test-retest reliability was found over a 10-week period with the normal sample. Support for the validity of the HSC was provided via studies with the suicide attempter group in which positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 25 publications
5
62
1
1
Order By: Relevance
“…The child is asked to agree or disagree with statements such as, "I want to grow up because I think things will get better." The scale has been developed using samples of children and adolescents with psychiatric disturbance, including depression [31,32], and it has demonstrated good internal consistency and construct validity [31]. Normative data are also available for healthy children [31,33].…”
Section: Participantsmentioning
confidence: 99%
“…The child is asked to agree or disagree with statements such as, "I want to grow up because I think things will get better." The scale has been developed using samples of children and adolescents with psychiatric disturbance, including depression [31,32], and it has demonstrated good internal consistency and construct validity [31]. Normative data are also available for healthy children [31,33].…”
Section: Participantsmentioning
confidence: 99%
“…Kazdin et al (1986) found that the HSC correlated positively with depression (r ϭ .58) and negatively with self-esteem (r ϭ Ϫ.61) and social skills (r ϭ Ϫ.39). Adequate internal consistency has been reported with clinical samples of children and young adolescents (e.g., 5 to 13 years old; ␣ ϭ .96; Kazdin et al, 1986), as well as older adolescents, including a study in which African American youth were included in the sample (e.g., 13 to 15 years old; ␣ ϭ .84; Spirito, Williams, Stark, & Hart, 1988); however, the alpha has been lower among community samples (e.g., ␣ ϭ .69; Spirito et al, 1988). To improve the alpha in our sample, we deleted items 1 ("I want to grow up, because I think things will be better"), 6 ("Some day, I will be good at doing the things that I really care about"), and 11 ("When I grow up, I think I will be happier than I am now") in the total hopelessness score.…”
Section: Measures Demographic Informationmentioning
confidence: 99%
“…A total sum is computed (with reverse coding where appropriate) to generate an overall score of hopelessness symptoms (α = .90 in this sample). Adequate internal consistency and validity have been demonstrated with adolescents (Spirito, Williams, Stark, & Hart, 1988). …”
mentioning
confidence: 99%